THE INVENTORY OF CAUSAL FACTORS CESSATION MEMBER OF â€œAKUâ€ CARD ON ALFAMART HASANUDIN SEMARANG - Hidayah, Arofani; Lubis, Nawazirul; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2013)
Network minimarket like Alfamart which engaged in franchising race to realizing an benefit minimarket. One strategy that has been done Alfamart procurement card is a AKU card of membership. AKU card intended as a form of marketing activity that seeks to spread information, affect / remind the target market of the company and its products to be willing to accept, purchase and loyalty to the products offered by Alfamart. Based on this formulation of the problem in this research is still visible deterioration member holder I significantly. This study aims to determine the factors that influence a customer's decision to quit as a member of the Mini Alfamart I Hasanudin Semarang and to determine which factors are more dominant in influencing the customer's decision to quit as a member of the Mini Alfamart I Hasanudin Semarang. This type of research is descriptive research by using primary data and secondary data. The data was collected using data collection instruments such as guiding question for obtaining data from the company, while to obtain data from 57 respondents using a questionnaire. The sampling technique used was purposive sampling. Furthermore, the data obtained from the field processed in tabular form to facilitate the processing and subsequent analysis. Data analysis method used is descriptive analytic. From these results it can be concluded that of the seven factors that cause the holder ceases to be a memberÂ  because first accidentally moved as many as 14 people or 24.56%, both as a competitor interest as many as 13 people or 22.81%, the third since the issue of service as many as 12 people or 21.05%, fourth due to customer dissatisfaction by 7 people or 12.28%, the fifth since the price as much as 6 people or 10.53%, the sixth since the quality of the product as much as 3 or 5.26% and the seventh since location as much as 2 or 3.51%. 7 Among the most dominant factor to cause the respondent ceased to be a member of AKU Alfamart Hasanudin Semarang is inadvertently changed factor as many as 14 people or 24.56%. Advice that can be given in this study is the company should continue to pay attention to the exterior display that influence consumers to buy. As the installation of banners discount / promo should be placed strategically so that more consumers can see them. Attempting to add back the diversity of products / goods are sold so that consumers easily get the products / items that they want. Rotating merchandise, product layout, and not to just focus on stagnan product or item. Providing training to the cashier about how intensive calculation engine operation, so as not to hinder the process of the transaction and cause queues.